Program of complex rehabilitation of pregnant with alimentary-constitutional obesity in the third trimester. - Kovalenko T.N; Lyannoy Y.O; Zhabchenko I.A (Kharkov National Pedagogical University, 2011)
In the article is presented the complex rehabilitation program for pregnant with alimentary-constitutional obesity in the third trimester. The program is directed on the decline of bodyweight, with the purpose of increase of scray-protective reactions of organism of pregnant and to the decline of obstetric traumatism in births. In an experiment took part 90 pregnant of the third trimester with obesity of I-III degree, middle genesial age. The developed and inculcated program foresaw the use of physical, psychological and medical rehabilitation.